Rethinking of international exchange and intercultural learning into Indonesian pre‐service teachers in the pandemic recovery: A narrative inquiry (Proceedings of English Linguistics and Literature, 2022)
One of teacher education goals is to produce interculturally competent educators; teach students in multicultural classrooms and prepare them in an increasingly globalized world. In response to this critical need in teacher preparation, international exchange attempts at developing those competencies. It is in accordance with Walters and Walters' (2009) principle, "Learning globally, teaching locally,". Despite the fact that the COVID-19 pandemic significantly restricted international student mobility over the past two years, many elements of life as it was before the pandemic are now returning. Certain pandemic rules remain in place, but students are now willing to travel abroad. Thus, this study explored the incorporation of international exchange and intercultural learning into seven Indonesian pre‐service teachers who mobilized in the Czech Republic. The data collected in this study were, questionnaires, participant diaries, and semi-structured interviews. The instruments were distributed during and after the program. This study utilized narrative analysis to comprehend the participants' stories. The results showed that through direct interaction with international communities, the participants become more culturally responsive human beings and in particular, as future educators. Future studies need to examine a longitudinal study on how the international experience shapes the participants' careers and ability to develop global consciousness in both objective and subjective metrics.